IDENTIFIKASI PERILAKU KONSUMTIF DAN KELEKATAN PENGGEMAR TERHADAP IDOL GROUP JKT48 DI KOMUNITAS TEAM48 KARAWANG - Muhammad Hafizh Ataurrahman, Arsi Widiandari (LP2M Universitas Muslim Nusantara Al Washliyah, 2026)
The popularity of idol groups often triggers consumptive behaviour among their fans. This can also be influenced by the attachment felt by fans towards their idols. This phenomenon is also found among fans of JKT48 (sister group of AKB48). Fans tend to spend money on purchasing merchandise even though these items are not considered basic necessities (clothing, food, shelter). The subjects of this study are JKT48 fans from the Team48 Karawang community who have a monthly income and exhibited consumptive behaviour towards purchasing merchandise and participating in fandom activities. This research uses a qualitative approach, including literature review and in-depth interviews, to explore consumptive behavior among fans. The results of this study reveal that consumptive behavior is influenced by emotional attachment to their idols. According to Jean Baudrillard’s theory of consumption, merchandise purchases are no longer based on their utility value but on their sign value, representing identity, loyalty, and fan existence. In line with John Bowlby’s attachment theory, the emotional bond between fans and idols creates a sense of closeness and the need to stay connected, triggering consumptive buying as a form of emotional expression and support for their idols.